(untitled) (Global Journal of Science Frontier Research, 2012)
In study we report synthesis Iodohydrines in absence of the complexes Schiff-base Salen Cu, Ni and Co.The experimental results showed both that the catalysts had higher catalytic activity and better epoxide selectivity than the homogeneous catalyst.